Description Of Rural Community Participation In Efforts To Prevent The Covid 19 Virus - Thamrin Pawalluri (Cita konsultindo, 2023)
The Covid 19 virus has not only spread in urban areas, but has also spread to remote villages. Even though urban areas are still areas with high transmission rates, this does not mean that rural communities do not have a risk of COVID-19 transmission. This study aims to describe community participation in villages in efforts to deal with the Covid-19 virus. journal articles as the main references studied. The results of this study show the diversity of rural community participation as a prevention effort to the spread of the Covid 19 virus, including following the rules set by the central government and local governments such as staying at home, maintaining distance, using masks, washing hands diligently and implementing healthy lifestyle, spraying disinfectants into residents' homes, and patterns of community interaction are intertwined due to actions, experience, knowledge, rational actions, and values ​​in village communities. In addition, rural communities as a system adapt to health protocol policies, build common goals to reduce the rate of spread of the virus, increase a sense of social solidarity, and as an effort to maintain, there are mask operations to always implement health protocols. Keywords: effort, participation, prevent, rural community, The covid 19 virus